2014
DOI: 10.1097/iae.0000000000000259
|View full text |Cite
|
Sign up to set email alerts
|

Malattia Leventinese/Doyne Honeycomb Retinal Dystrophy in a Chinese Family With Mutation of the Efemp1 Gene

Abstract: The R345W mutation in EFEMP1 caused Malattia leventinese/Doyne honeycomb retinal dystrophy in a Chinese family. This is the first report, as per our knowledge, of the R345W mutation in EFEMP1 in a Chinese pedigree of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Previous ocular genetic studies have identified a recurrent, missense mutation in exon-10 of EFEMP1 (c.1033C>T, p.R345W) associated with Doyne honeycomb retinal dystrophy (DHRD) and/or Malattia Leventinese (MLVT, MIM: 126600) in European and Asian families [ 11 , 20 24 ]. Recently, a novel intronic variant of unknown significance in EFEMP1 was reported in a DHRD patient [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous ocular genetic studies have identified a recurrent, missense mutation in exon-10 of EFEMP1 (c.1033C>T, p.R345W) associated with Doyne honeycomb retinal dystrophy (DHRD) and/or Malattia Leventinese (MLVT, MIM: 126600) in European and Asian families [ 11 , 20 24 ]. Recently, a novel intronic variant of unknown significance in EFEMP1 was reported in a DHRD patient [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, besides remarkable drusen, there were large dark gray lesions originated from RPE/choroid atrophy in the posterior pole around the disc. No such feature was reported in the previous literature, even a few cases presented pigment proliferation in the macula [1114]. Thirdly, the vision of the patient and her brother was not significantly impaired despite of the wide damages in the fundus.…”
Section: Discussionmentioning
confidence: 80%
“…To date, there were few reports of ML/DHRD. In China mainland, there was only one case report of R345W mutation in EFEMP1 caused ML/DHRD in a family [14]. In that report, 6 members of one family at the age of 37–61 yrs., and the proband was 43 yrs., all of whom showed drusen distributed in the fundus, 2 had RPE disorders and CNV.…”
Section: Discussionmentioning
confidence: 99%
“…La variante patogénica p.Arg345Trp, identificada en esta familia, es la única asociada con la enfermedad hasta el momento en diferentes poblaciones 1 , 5 - 8 . En los estudios en pacientes de diferentes etnias, solo una vez se logró determinar esta variante en un ancestro común de origen suizo 1 .…”
Section: Discussionunclassified
“…La malattia leventinese fue descrita por primera vez en individuos originarios del valle Leventina, en el sur de Suiza, de ahí su nombre 5 . Hasta el momento, solo se ha reportado una variante patogénica en el gen EFEMP1 como causante de la enfermedad, la c.1033C>T/p.Arg345Trp 1 , 6 , 7 , la cual se ha detectado en población sueca, británica, australiana, norteamericana, japonesa y coreana 8 .…”
unclassified